2017
DOI: 10.1111/ijpp.12424
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the career choices of White and Black, Asian and Minority Ethnic women pharmacists: a qualitative study

Abstract: ObjectiveIn the UK, a growing number of females entering pharmacy are women from Black, Asian and minority ethnic groups (BAME). Research shows that BAME women are more likely to work in the community sector and be self‐employed locums than white women, and Asian women overrepresented in part‐time, lower status roles. This study aims to explore the employment choices of white and BAME women pharmacists to see whether their diverse work patterns are the product of individual choices or other organisational fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Earlier research by Hussein et al (2014) shows that employers in social care reported recruiting significantly higher proportions of minority workers through employment agencies. These variations in the reliance on recruitment agencies among minority and migrant individuals are linked to weak social capital and poor labour market connections and reflect the wider disadvantaged position of racialised individuals within the societal structure (Figgett, 2017;Hussein and Christensen, 2017;Howells et al, 2018;Sahraoui, 2019).…”
Section: Recruitmentmentioning
confidence: 99%
“…Earlier research by Hussein et al (2014) shows that employers in social care reported recruiting significantly higher proportions of minority workers through employment agencies. These variations in the reliance on recruitment agencies among minority and migrant individuals are linked to weak social capital and poor labour market connections and reflect the wider disadvantaged position of racialised individuals within the societal structure (Figgett, 2017;Hussein and Christensen, 2017;Howells et al, 2018;Sahraoui, 2019).…”
Section: Recruitmentmentioning
confidence: 99%
“…Cultural differences in normative practices for choosing careers, including pharmacy, have been reported and it is possible that cultural influences on leaving pharmacy may exist in New Zealand. 23,27,28 However, we were unable to explore this in our study and further research is warranted. Resource constraints limited the study to only ten interviews of purposively chosen respondents.…”
mentioning
confidence: 82%
“…Within the UK, and more widely, BAME individuals comprise a growing proportion of the workforce (Atewologun, 2018). In particular, statistics show that BAME women are entering occupations such as law, professional services and pharmacy (Atewologun, 2018;Aulack et al, 2017;Howells et al, 2018). Despite these trends in the occupational choices of BAME women, they have been largely absent from research into occupational choice -with the focus more on women's choices or BAME employees' choices, rather than both.…”
Section: The Careers Of Bame Women and Intersectional Analysismentioning
confidence: 99%
“…It provides a particularly relevant context in which to study the careers of BAME women since it has, over time, become ethnically diverse and feminised and is therefore well suited to addressing the research aims. In 2017, women comprised 62 percent and BAMEs comprised 49 percent of registered UK pharmacists; both have been steadily increasing and these trends are predicted by the General Pharmaceutical Council to continue (Howells et al, 2018). To qualify as a pharmacist requires a four-year degree followed by a one-year pre-registration vocational training course in a sector of pharmacy.…”
Section: Research Settingmentioning
confidence: 99%